Enabling the scaling of evidence-based climate-smart agriculture technologies and innovations in West Africa and the Sahel - Kpadonou, G Esaie; Ganyo, Komla Kyky; Segnon, Alcade Christel; Ouedraogo, Harouna; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
Reorienting agricultural practices is essential for enabling climate-resilient and low-emission food systems through climate-smart agriculture (CSA). AICCRA and FSRP programs have been collaborating to scale climate smart-agriculture in Africa through capacity building and promotion of evidence-based CSA technologies and innovations. This deliverable reports the outcomes of the demand-drivenpractical training-action workshop targeting FSRP countries stakeholders on CSA identification and prioritization. 35 participants (07 women) from 08 FSRP countries (05 non-AICCRA countries) in West Africa and Sahel attended the action-training workshop. Through AICCRA technical capacity building and action-oriented engagement, each FSRP country has successfully applied the CSA Prioritization Framework (CSA-PF) to evaluate the climate-smartness of technologies and innovations being deployed in each country. The outcomes are compiled in 08 CSA country briefs, guiding the FSRP implementation in each country. Through AICCRA technical capacity building and action-oriented engagement, each FSRP country has successfully applied the CSA Prioritization Framework (CSA-PF) to evaluate the climate-smartness of technologies and innovations being deployed in each country. The outcomes are compiled in 08 CSA country briefs, guiding the FSRP implementation in each country. Bundled CSA technology packages deliver stronger resilience outcomes: combining seeds, inputs, mechanization, and soil water management practices, supported by access to climate information proves more effective than isolated interventions.